2011
DOI: 10.1186/1756-8722-4-54
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and in vitro propagation of infantile hemangioma stem cells and an in vivo mouse model

Abstract: BackgroundInfantile hemangiomas (IH) are the most common benign tumors of infancy. The typical clinical course consists of rapid growth during the first year of life, followed by natural and gradual involution over a multi-year time span through unknown cellular mechanisms. Some tumors respond to medical treatment with corticosteroids or beta-blockers, however, when this therapy fails or is incomplete, surgical extirpation may be necessary. Noninvasive therapies to debulk or eliminate these tumors would be an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…These results demonstrate that IH-derived stem cells are the cellular precursors of IHs. Similar results were found by Xu et al [54].…”
Section: Increased Angiogenic and Vasculogenic Activitysupporting
confidence: 92%
“…These results demonstrate that IH-derived stem cells are the cellular precursors of IHs. Similar results were found by Xu et al [54].…”
Section: Increased Angiogenic and Vasculogenic Activitysupporting
confidence: 92%
“…Overall, CMN colonies could be maintained for at least 84 days in vitro. Similarly, tumor-propagating cells have been reported in other benign cutaneous proliferations such as papilloma and hemangioma (Khan et al, 2008;Xu et al, 2011;Lapouge et al, 2012). Beyond in vitro studies, maintaining properties were studied in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, HemSCs may contain both of Hem-MSCs and HemEPCs. Studies from different groups have demonstrated that HemSCs have the ability to self-renew and can differentiate into endothelium, adipocytes and pericytes in vitro [15,20]. When implanted subcutaneously into nude mice, HemSCs can produce human glucose transporter-1 (GLUT-1) positive microvessels at 7-14 days [15,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%